Fluorescent cross-linked polystyrene perylenebisimide/oligo(p-phenylenevinylene) microbeads with controlled particle size, tunable colors, and high solid state emission - Sonawane, Swapnil L.; Asha, S. K. (ACS Applied Materials & Interfaces, 2013)
A series fo cross-linked fluorescent polystyrene (PS) microbeads with narrow size distribution and intense solid state emission was developed. Fluorophores based on perylene bisimide (PBI) and oligo(p-phenylenevinylene) (OPV) designed as acrylic cross-linkers were introduced into the polymerization recipe in a twostage dispersion polymerization, carried out in ethanol in the presence of poly(vinylpyrrolidone) (PVP) as stabilizer. The structural design permitted introduction of up to 10(-5) moles of the fluorophores into the polymerization medium without fouling of the dispersion. The particle size measured using dynamic light scattering (DLS) indicated that they were nearly monodisperse with size in the range 2-3 mu m depending on the amount of fluorophore incorporated. Fluorescence microscope images of ethanol dispersion of the sample exhibited intense orange red emission for PS-PBI-X series and green emission for PS-OPV-X series. A PS incorporated with both OPVX and PBIX exhibited dual emission upon exciting at the OPV wavelength of 350 nm and PBI wavelength of 490 nm, respectively. The low incorporation of fluorophore resulted in almost complete absence of aggregation induced reduction in fluorescence as well as red-shifted aggregate emission. The solid state emission quantum yield measured using integrating-sphere setup indicated a very high quantum yield of phi(powder) = 0.71 for PSOPV-X and phi(powder) = 0.25 for PS-PBI-X series. The cross-linked PS microbeads incorporating both OPV and PBI chromophores had a phi(powder) = 0.33 for PBI emission and phi(powder) = 0.20 for OPV emission. This strategy of introducing fluorophore as crosslinkers into the PS backbone is very versatile and amenable to simultaneous addition of different suitably designed fluorophores emitting at different wavelengths.
Keywords: dispersion polymerization; dual emission; fluorescent cross-linker; oligo(p-phenylenevinylene); Perylenebisimide; solid state fluorescence